The Impact of Road Development on Household Welfare in Rural Papua New Guinea - Martin Wiegand; Eric Koomen; Menno Pradhan; Christopher Edmonds (Tinbergen Institute, 2017)
In this paper we estimate the impact of road development on household welfare in rural Papua New Guinea over the period between 1996 and 2010, using two cross-sectional household surveys and corresponding road maps. To deal with endogenous placement of road infrastructure programs we employ a correlated random effects model that corrects for location-specific changes in road quality. We also use a newly developed quantile regression method to investigate whether road works are pro-poor. Estimates show that investments in sealing roads to nearest towns led to higher consumption levels and housing quality, and to less reliance on subsistence farming. Effects are stronger among poor, less educated, and female-led households.
Keywords: H54; O18; 330; roads; infrastructure; impact evaluation; household welfare; developing country; Papua New Guinea